Quantitative Helmint Assesment (QHA) On Nutritional Status of Children and Stunting Events For Elementary Students in the City Of Makassar - Alfina Baharuddin; A. Nurlinda; Suharni A. Fachrin (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: to analyze the relationship between the Quantitative Helmint Assessment with nutritional statusand the incidence of stunting in SD Bangkala III students in Makassar CityMethod :This type of research is analytic observational using cross sectional design. Location This researchwas conducted at SD Bangkala III, Bangkala Village, Manggala District, Makassar City. 63 samples weretaken using proportional stratified random sampling technique and simple random sampling. Quantitativeexamination is needed to determine the intensity of infection or severity of disease by knowing the numberof eggs per gram of feces (EPG) in each type of worm.Results: based on the measurement results of the helmint assessment for the mild category with the incidenceof stuting and not stunting kneeling as many as 8 (38.0%), 13 (62.0%), respectively. In the measurementresults, the moderate category with the incidence of stuting and non-stunting was 11 (38%), respectively. 13(62%), while the results of QHA measurements for the severe category of knee stunting were 1 (25%), and 3(75%), respectively. based on the measurement results of the helmint assessment for the light category withnutritional status of thin, normal and obese knees as many as 5 (23.8%), 13 (62.0%) and 3 (14.2%).Conclusion: There is a significant relationship between QRA and nutritional status in elementary schoolstudents with p value (0.003), there is a significant relationship between QRA and the incidence of stuntingwith p value (0.022).